Liouville's equations for random systems - Jornet, Marc (Stochastic analysis and applications, 2022)
Given a random system, a Liouville's equation is an exact partial differential equation that describes the evolution of the probability density function of the solution. In this article, we derive Liouville's equations for the first-order homogeneous semilinear random partial differential equation. This is done for all finite-dimensional distributions of the random field solution, starting with dimension one, then dimension two, and finally generalizing to any dimension. Several examples, including the linear advection equation with random coefficients, are treated. As a corollary, we deduce Liouville's equations for path-wise stochastic integrals and nonlinear random ordinary differential equations.